<htm>Fungos gasteroides no Rio Grande do Sul, Brasil: Arachnion e Disciseda (Lycoperdaceae) </htm> - Cortez, Vagner G.; Baseia, Iuri G.; Silveira, Rosa Mara B. da (Acta Biológica Paranaense, 2010)
Fungos gasteroides no Rio Grande do Sul, Brasil: Arachnion e Disciseda (Lycoperdaceae)